Within- and between-subject biological variation data for whole blood HbA 1c from 38 apparently healthy Turkish subjects - Keleş, Murat; Ünver Şeker, Gönül (Scandinavian journal of clinical and laboratory investigation, 2024)
HbA plays an important role in the diagnosis and treatment of diabetes and is a valuable biomarker for evaluating glycemic control and predicting the risk of vascular complications. The study aimed to determine the biological variation (BV) for HbA and thereby contribute to analytical performance specifications, reference change values, and index of individuality. Fasting venous whole blood samples were collected from 38 presumably healthy subjects (20 females, 18 males) once a week for ten weeks, and analyzed in duplicate using the Roche Cobas c501 analyzer. BioVar, an online R-based biological variation analysis tool, was used for the statistical analysis. BV values were obtained by analysis of variance (ANOVA) after outlier detection, normality tests, steady-state, and homogeneity checks. The within-subject biological variation for HbA was 2.9%, and the between-subject biological variation was 7.9%. The index of the individuality of HbA was 0.37. Derived desirable analytical goals for imprecision, bias, total allowable error, and maximum expanded allowable measurement uncertainty were 1.4%, 1.8%, 4.2%, and 2.9% respectively. The reference change value is more appropriate for interpreting HbA1c results than a population-based reference interval.